FORMATION OF ANALYTICAL THINKING IN PRESCHOOL CHILDREN THROUGH FAIRY TALES - Sharobidin Khasanov Azamovich (Scholar Express Journal, 2021)
The article discusses the formation of analytical thinking of preschool children through fairy tales.
Keywords: Thinking; analytical thinking; civilization; synthesis